New Zealand's "arc of influence": the "clean, blue, green" country. Issue 3 (2nd September 2018) - Abbott, Mick; Boyle, Cameron; Blackburne, Kate; Lee, Woody
ABSTRACT: Over the last 50 years, the area of New Zealand has been expanded to include territorial seas, an Exclusive Economic Zone, marine protected areas, an extended continental shelf, the Ross Sea, and a wedge of the Antarctic continent. While New Zealand's territory is now significantly more marine rather than terrestrial, the country is often imagined as a series of isolated islands floating adrift in the Pacific. In this paper, we consider how the space of the nation-state can be reimagined to create a more relevant sense of place and identity. We argue that the perception of New Zealand as "100% pure" and "clean green" can be developed into a "clean, blue, green" image that better reflects the country's expansive and diverse "arc of influence" through conservation values. We focus on the role of mapping within this issue; critiquing existing maps of New Zealand's marine territory while also presenting our own speculative maps.